Building a Networked Improvement Community: Lessons in Organizing to Promote Diversity, Equity, and Inclusion in Science, Technology, Engineering, and Mathematics - Noble, Chelsea E.; Amey, Marilyn J.; Colón, Luis A.; Conroy, Jacqueline; De Cheke Qualls, Anna; Deonauth, Kamla; Franke, Jeffrey; Gardner, Alex; Goldberg, Bennett; Harding, Thelma; Harris, Gary; Hernández, Sara Xayarath; et al. (Frontiers in Psychology, 2021)
In 2016, ten universities launched a Networked Improvement Community (NIC) aimed at increasing the number of scholars from AGEP populations entering STEM faculty careers. NICs bring together stakeholders focused on a common goal to accelerate innovation through structured, ongoing intervention development, implementation, and refinement. We theorized a NIC organizational structure would aid understandings of a complex problem in different contexts and accelerate opportunities to develop and improve interventions to address the problem. A distinctive feature of this NIC is its diverse institutional composition of public and private, predominantly white institutions, a historically Black university, a Hispanic-serving institution, and land grant institutions located across 8 states and Washington, D.C. NIC members hold different positions within their institutions and have access to varied levers of change. Among the lessons learned, analyzing and addressing failed strategies is as equally important to a healthy NIC as is sharing learning from successful interventions. We initially relied on pre-existing relationships and assumptions about how we would work together, rather than making explicit how the NIC would develop, establish norms, understand common processes, and manage changing relationships. We had varied understandings of the depth of campus differences, sometimes resulting in frustrations about the disparate progress on goals. NIC structures require significant engagement with the group, often more intensive than traditional multi-institution organizational structures. They require time to develop and ongoing maintenance in order to advance the work. We continue to reevaluate our model for leadership, climate, diversity, conflict resolution, engagement, decision-making, roles, and data, leading to increased investment in the success of all NIC institutions. Our NIC has evolved from the traditional NIC to become the CIRTL AGEP NIC model with five key characteristics 1) a well-specified aim, 2) understanding of systems, including the variety of contexts and different organizations, 3) a culture and practice of shared leadership and inclusivity, 4) use of data reflecting different institutional contexts, and 5) ability to accelerate infrastructure and interventions. We conclude with recommendations for those considering developing a NIC to promote diversity, equity, and inclusion efforts.